Potassium aluminium sulphate (Alum) inhibits growth of human axillary malodor-producing skin flora in vitro / Hassanain Al-Talib ... [et al.] - Al-Talib, Hassanain; Mohd Nasir, Nur Izzati Syamimi; Yaziz, Hafizuddin; Zulkafli, Nur Fatihah; Adani, Nur Aqidah; Noor Rashidi, Ahmad Ikhwan; Murugaiah, Chandrika; Shaari, Syahrul Azlin (Faculty of Medicine, 2016)
Introduction: Axillary malodor is caused by microbial biotransformation of non-smelling molecules present in apocrine secretions, into volatile odorous molecules. This study aimed to determine the antimicrobial activities of potassium aluminium salts (alum) against four malodor-producing axillary bacterial flora, as an alternative natural product for reducing axillary malodor. Methods: The antimicrobial activity of alum against axillary bacterial flora [Micrococcus luteus (ATCC 49732) (M. luteus), Staphylococcus epidermidis (ATCC 14990) (S. epidermidis), Corynebacterium xerosis (ATCC BAA-1293) C. xerosis and Bacilus subtilis (ATCC 19659) (B. subtilis)], was tested in vitro using broth dilution method for different concentrations (0.937 - 20mg/mL) on Luria-Bertani broth. Subculture was done to determine colony-forming units (CFUs) and the minimum inhibitory concentrations (MICs). Results: Alum showed excellent inhibitory effects on all tested bacteria. The lowest MIC of alum was against C. xerosis, at 1.88 mg/mL. M. luteus, B. subtilis and S.epidermidis showed a higher MIC of 3.75, 5.00 and 7.50 mg/mL, respectively. All of the tested bacteria were completely inhibited at a concentration of 7.50 mg/mL. Conclusions: This study revealed that alum has excellent antimicrobial effects against axillary malodor -producing bacteria and is recommended to be used either directly by topical application or as an active ingredient in deodorants and antiperspirants.